2007
DOI: 10.1111/j.1540-8183.2007.00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience of StarClose Vascular Closure Device in Patients with First and Recurrent Femoral Punctures

Abstract: Our study found no major complications but a 10% failure rate and a 9.7% rate of minor complications. Close surveillance is important as there is a risk for recurrent bleeding, especially in patients with partial device success as defined in this report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
3
11
1
Order By: Relevance
“…The 7.1% major vascular complication rate attributable to StarClose in this study was higher than previously reported 0–4.1% [2,3,4,5,6,9,18,19,20,21,22,23,24], but the minor 11.9% complication rate was within the range of 2.1–27%, even though the device was used for closing larger puncture holes.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The 7.1% major vascular complication rate attributable to StarClose in this study was higher than previously reported 0–4.1% [2,3,4,5,6,9,18,19,20,21,22,23,24], but the minor 11.9% complication rate was within the range of 2.1–27%, even though the device was used for closing larger puncture holes.…”
Section: Discussioncontrasting
confidence: 71%
“…The 88.1% device success rate of this study was within the range of the 87–94% device success rate [3,9,18,19,20,21], but the 92.9% was slightly lower than the 96–100% procedural success rate [2,3,19,20,21,22,23] reported for the same device in 5-, 6- or 7-Fr punctures. The 7.1% major vascular complication rate attributable to StarClose in this study was higher than previously reported 0–4.1% [2,3,4,5,6,9,18,19,20,21,22,23,24], but the minor 11.9% complication rate was within the range of 2.1–27%, even though the device was used for closing larger puncture holes.…”
Section: Discussionsupporting
confidence: 60%
“…Tay et al reported their experience with repeat closure in 25 patients undergoing coronary interventions. 7 The device success (96%) and low complication rates (8%) were encouraging.…”
Section: Discussionmentioning
confidence: 79%
“…Procedural success was 95.7% and complication rates are in keeping with those reported in studies of patients undergoing cardiac and peripheral vascular procedures. [1][2][3][4][5][6][7][8] Rates of groin hematomas in both the manual closure (4.2%) and StarClose (1.4%) groups were similar.…”
Section: Discussionmentioning
confidence: 99%
“…1). The sheath is a 6 F sheath with a sidearm that is introduced into the target vessel and then used as a passageway for the insertion of diagnostic, guide, or other interventional catheters [9][10][11]. The angiography of femoral arteries was not executed before the implantation of the StarClose clip.…”
Section: Procedures (Protocol) Description In Group IImentioning
confidence: 99%